phân tích đa thức thành nhân tử 12y-9x^2+36-3x^2y

Photo of author

By Camila

phân tích đa thức thành nhân tử 12y-9x^2+36-3x^2y

0 bình luận về “phân tích đa thức thành nhân tử 12y-9x^2+36-3x^2y”

  1. $12y-9x^2+36-3x^2y$

    $=(12y-3x^2y)+(36-9x^2)$

    $=3y.(4-x^2)+9.(4-x^2)$

    $=(3y+9).(4-x^2)$

    $=3(y+3).(2-x).(2+x)$

  2. `12y-9x^2+36-3x^2y`

    `=(12y-3x^2y)-(9x^2-36)`

    `=3y(4-x^2)-9(x^2-4)`

    `=3y(4-x^2)+9(4-x^2)`

    `=(3y+9)(4-x^2)`

    `=3(y+3)(2-x)(2+x)`

Viết một bình luận